1999
DOI: 10.1136/jnnp.66.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spondylotic myelopathy in elderly people: a high incidence of conduction block at C3-4 or C4-5

Abstract: Objectives-To precisely localise the site of conduction block in elderly patients with cervical spondylotic myelopathy in the presence of multilevel compression shown by MRI. Methods-A total of 44 patients aged 65 and older underwent serial intervertebral recording of spinal somatosensory evoked potentials (SSEPs) from either the intervertebral disc or the ligamentum flavum after epidural stimulation. The site of conduction block identified by abrupt reduction in size of the negative peak was designated as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 45 publications
4
27
0
1
Order By: Relevance
“…Another assumption is that recovery from long-tract signs such as gait disturbance may be more marked if the decompression area is large and cranial. The intervertebral levels involved, as determined by radiographic and electrophysiological analyses in elderly patients, were previously reported to be C3-C4 or C4-C5 [16][17][18][19][20], and the results of this study concur with this. If this theory is correct, elderly patients may achieve satisfactory recovery because the primary lesion can be located more cranially in these patients than in younger patients.…”
Section: Discussionsupporting
confidence: 82%
“…Another assumption is that recovery from long-tract signs such as gait disturbance may be more marked if the decompression area is large and cranial. The intervertebral levels involved, as determined by radiographic and electrophysiological analyses in elderly patients, were previously reported to be C3-C4 or C4-C5 [16][17][18][19][20], and the results of this study concur with this. If this theory is correct, elderly patients may achieve satisfactory recovery because the primary lesion can be located more cranially in these patients than in younger patients.…”
Section: Discussionsupporting
confidence: 82%
“…Some elderly subjects are diagnosed with asymptomatic spinal cord compression in radiological findings. 21 Some authors reported that measurement of CMCT was valuable for diagnosis of CCM and CTM. 2,3,22 CCM consists of cervical spondylotic myelopathy (CSM), ossification of the posterior longitudinal ligament (OPLL), and other degenerative disease.…”
mentioning
confidence: 99%
“…17 Elderly patients with cervical spondylotic myelopathy show multiple cord compression on MRI, but SCEPs usually showed a single level of conduction block and 95% of focal conduction block at the C3/4 or C4/5 level. 18 Azuma et al 19 reported that 78% of patients with cervical ossification of the posterior longitudinal ligament were determined by SCEPs to have a single site of conduction abnormalities and in about 70% the level was C3/4 or C4/5; however, they found multiple cord compression. These reports indicate multiple compression of the spinal cord on radiographic findings can include clinically silent compression.…”
Section: Discussionmentioning
confidence: 99%